Disclosure quality ratings by the stock exchanges: evidence from China - Shuo Yang; Jingran Zhao (China Accounting and Finance Review)
The stock exchanges in China assess firms’ disclosure quality annually according to a grading sheet. The grading sheet evaluates mandatory and voluntary disclosures, investor relations, and compliance with and violations of securities laws; some items are publicly observable, others are either not publicly observable or require managerial discretionary judgement. This paper examines whether the ratings simply summarize easily observable public signals of disclosure quality or offer information less accessible to investors. We regress raw ratings on public signals on the grading sheet and obtain the residuals as excess ratings. We examine the association between excess ratings and market-based and accounting-based information quality measures to verify that excess ratings are not noises. We further examine whether the market response to the announcement of ratings is associated with excess ratings and whether excess ratings are predictive of future outcomes. We find that the market response to the announcement of the assessment result is not related to excess ratings. Excess ratings are associated with several market-based and accounting-based information quality measures, suggesting that they are not noises. Excess ratings are predictive of an array of outcomes in the following year, including institutional ownership, analyst coverage, analyst forecast accuracy and dispersion, and securities enforcement. We carefully examine the items on the grading sheet and obtain excess ratings orthogonal to easily observable public signals. We find that excess ratings contain private information about firms’ fundamentals and compliance with securities laws which investors cannot easily observe or access, but investors ignore this information.